Regular Open Sets on The Intuitionistic Fuzzy Topological Spaces in Sostak's Sense - T. Menagadevi; P. Maragatha Meenakshi; Neelamegarajan Rajesh (Journal of the Indonesian Mathematical Society, 2023)
The aim of this paper is to introduce and study the concepts of intuitionistic r-fuzzy regular open sets and their related notions in topological spaces.